Transformation of adenocarcinoma into small cell lung cancer as one of the mechanisms of acquired resistance to anti-EGFR tyrosine kinase inhibitors - O. O. Kovalov; O. P. Tolok; K. O. Kovalov (Patologìâ)
Transformation of adenocarcinoma into small cell lung cancer (SCLC) is a rare and unique biological property of a cancer cell that is responsible for the mechanism of acquired resistance to EGFR tyrosine kinase inhibitors.